2012
DOI: 10.2466/24.pms.114.2.527-541
|View full text |Cite
|
Sign up to set email alerts
|

Visual Assessment of Camouflaged Targets with Different Background Similarities

Abstract: The study investigated the effectiveness of different camouflage designs using a computational image quality index. Camouflaged human targets were presented on a natural landscape and the targets were designed to be similar to the landscape background with different levels of background similarity as estimated by the image index. The targets were presented in front of the observer (central 0 degrees) or at different angles in the left (-7 degrees, -14 degrees, -21 degrees) or right (+7 degrees, +14 degrees, +2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…These metrics allowed us to distinguish between good (patterns 1, 8, 9, 11 in Fig. 4), medium (patterns 5, 6, 10) and poorly performing patterns (2,3,4,7). The pattern based on the design method presented here (pattern number 9) combined the overall lowest detection probability with an intermediate search time, indicating that the TNO design method can produce effective camouflage patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These metrics allowed us to distinguish between good (patterns 1, 8, 9, 11 in Fig. 4), medium (patterns 5, 6, 10) and poorly performing patterns (2,3,4,7). The pattern based on the design method presented here (pattern number 9) combined the overall lowest detection probability with an intermediate search time, indicating that the TNO design method can produce effective camouflage patterns.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Traditionally camouflage design was (and still is) largely based on intuition and aesthetics, and was performed by industrial designers and (especially in the beginning) by artists 6 (incl. cubists such as Georges Braque).…”
Section: Introductionmentioning
confidence: 99%
“…A review of elevation-dependent warming and its possible causes in four high mountain regions–the Swiss Alps, the Colorado Rocky Mountains, the Tibetan Plateau/Himalayas, and the Tropical Andes–showed variation in the trends of extreme temperatures suggesting the need for a comprehensive study analysing the minimum and maximum temperatures separately for all mountain regions together to better understand elevation-based warming in mountains [122]. The highly varied topography over short distances and poor coverage of observational datasets especially in mountain regions render spatiotemporal climate change projections for Nepal difficult and any projections must be interpreted with caution [123].…”
Section: Discussionmentioning
confidence: 99%
“…Our choice of placing all targets in identical position in a scene also reduces the image edging effect on the target rankings. It has been reported that observers tend to focus on the center of an image [17], resulting in differences in detection performance by the observers [2,17,19].…”
Section: Choosing Scenes and Their Corresponding Weightsmentioning
confidence: 99%
“…Photo-simulation by using human observers as an assessment method of camouflage effectiveness has been used in various forms in the recent decades [1][2][3][4]. Other methodologies have also been tested out, involving video surveillance [5], simulation of human vision [6][7][8][9][10][11], similarity measures of target-background by image analysis techniques [2,11], assessment by simulation of target vehicles against different backgrounds [12], and image sequences taken by approaching sensors [13].…”
Section: Introductionmentioning
confidence: 99%